2008
DOI: 10.1002/job.518
|View full text |Cite
|
Sign up to set email alerts
|

Commitment, procedural fairness, and organizational citizenship behavior: a multifoci analysis

Abstract: SummaryResearch on commitment, procedural fairness, and organizational citizenship behavior (OCB) suggests that employees maintain distinct beliefs about, and direct behaviors towards, multiple targets in the workplace (e.g., the organization as a whole, their supervisor, and fellow workgroup members). The present studies were designed to test for ''target similarity effects,'' in which the relationships between commitment, procedural fairness, and OCB were expected to be stronger when they referred to the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
190
5
12

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(230 citation statements)
references
References 55 publications
11
190
5
12
Order By: Relevance
“…For example, Salehi and Gholtash (2011) in Iran showed that variable of organizational commitment had a positive effect on the OCB. Also, a review of the previous studies such as Meyer and Allen (1990), Ensher et al (2001), Gautam et al (2005), Haigh and Pfau (2006), Liu (2009), Lavelle et al (2009), Ng and Feldman (2011, Morin et al (2011), Chen andKao (2012), and Islam et al (2012) indicates that positive OCB is effective on organizational commitment. Therefore, these results show that physical education managers, based on the proposed strategies, should be able to increase rate of staff's organizational commitment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Salehi and Gholtash (2011) in Iran showed that variable of organizational commitment had a positive effect on the OCB. Also, a review of the previous studies such as Meyer and Allen (1990), Ensher et al (2001), Gautam et al (2005), Haigh and Pfau (2006), Liu (2009), Lavelle et al (2009), Ng and Feldman (2011, Morin et al (2011), Chen andKao (2012), and Islam et al (2012) indicates that positive OCB is effective on organizational commitment. Therefore, these results show that physical education managers, based on the proposed strategies, should be able to increase rate of staff's organizational commitment.…”
Section: Discussionmentioning
confidence: 99%
“…Haigh and Pfau (2006), in a study entitled ''Bolstering organizational identity, commitment, and citizenship behaviors through the process of inoculation'' concluded that organizational identity, organizational commitment, and certain OCBs could be strengthened through internal communication (Haigh and Pfau 2006). Lavelle et al (2009), in their study entitled ''Commitment, procedural fairness, and organizational citizenship behavior: a multifocal analysis'' concluded that: (1) the positive relationship between commitment and OCB, and (2) the mediating effect of commitment on the positive relationship between procedural fairness and OCB were particularly likely to emerge when the constructs referred to the same target. Support of these target similarity effects was found among layoff survivors (Study 1) and student project teams (Study 2), (Lavelle et al 2009).…”
Section: Organizational Citizenship Behavior and Organizational Commimentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have demonstrated how procedural fairness matters beyond the legal context, including in educational (Tyler & Caine 1981), managerial (Lavelle et al 2009), and political (Tyler 1994;Bøggild 2014) settings. Figure 1 reports six widely considered procedural criteria.…”
Section: Procedural Fairness: Existing Findings and Theorymentioning
confidence: 99%
“…Organizational commitment is a widely researched and extremely promising relational construct [7], [8] [49]. The last two hypotheses of the study are proposed:…”
Section: The Mediating Role Of Organizational Commitmentmentioning
confidence: 99%